Measurement of the Varus Thrust of a Single-Leg Standing Position Using Strain Sensors: Determining the Effectiveness of Knee Orthosis - Yamamoto, Hiroaki; Mori, Masahiro; Tashiro, Koichi; Endo, Masahide; Kitagawa, Kodai (Journal of Prosthetics Orthotics and Science Technology, 2025)
Background: Osteoarthritis of the knee is based on degenerative changes in the articular cartilage, resulting in varus thrust. Therefore, the treatment involves orthosis therapy to reduce the mechanical stress. Aims: The varus thrust of a young healthy subject is measured. Then, the relationship between orthosis and varus thrust is clarified. The purpose of this study was to assist in orthosis therapy for patients with knee osteoarthritis. Methods: The subjects were 15 young healthy subjects. The varus thrust during single-leg standing with and without orthosis was measured by strain sensors. Comparisons between groups were analyzed using the Wilcoxon rank-sum test. The statistical software fair was JSTAT for Windows, and the significance level was set at 5%. Results: Significant differences in strain sensor elongation were found between the groups with and without the orthosis. Conclusion: It was confirmed that the knee orthosis suppressed the varus thrust. The future challenge is to measure patients with knee osteoarthritis.